Temporal Profiling of Cellular and Molecular Processes in Osteodifferentiation of Dental Pulp Stem Cells - Bibiána Baďurová; Kristina Nystøl; Terézia Okajček Michalič; Veronika Kucháriková; Dagmar Statelová; Slavomíra Nováková; Ján Strnádel; Erika Halašová; Henrieta Škovierová (Biology)
Based on the potential of DPSCs as the most promising candidates for bone tissue engineering, we comprehensively investigated the time-dependent cellular and molecular changes that occur during their osteodifferentiation. To analyze this area in-depth, we used both cellular and molecular approaches. Morphological changes were monitored using bright-field microscopy, while the production of mineral deposits was quantified spectrophotometrically. The expression of a key mesenchymal stem cell marker, CD90, was assessed via flow cytometry. Finally, protein-level changes in whole cells were examined by fluorescence microscopy. Our results show successful long-term osteodifferentiation of the patient’s DPSCs within 25 days. In differentiated cells, mineralized extracellular matrix production gradually increased; in contrast, the expression of the specific stem cell marker CD90 significantly decreased. We observed dynamic changes in intracellular and extracellular proteins when collagen1 A1 and osteopontin appeared as earlier markers of osteogenesis, while apolipoprotein A2, bone morphogenetic protein 9, dentin sialophosphoprotein, and matrix metalloproteinase 8 were produced mainly in the late stages of this process. A decrease in actin microfilament expression indicated a reduction in cell proliferation, which could be used as another marker of osteogenic initiation. Our results suggest a coordinated process in vitro in which cells synthesize the necessary proteins and matrix components to regulate the growth of hydroxyapatite crystals and form the bone matrix.